27.0k views
4 votes
What is the solution of the system use substitution 3x + 2y equals 7 y =
3 - 3x + 11​

User Jblasco
by
5.7k points

2 Answers

7 votes

Answer: The answer is 7.

Step-by-step explanation: Okay. so y = 3 - 3x + 11.

Equation: 3x + 2y = 7

Another way of writing this is:

3x + 2(3 - 3x + 11) which translates to:

3x + 6 - 6x + 22 = 7

Add the numbers together, and you get this:

3x = 21

Divide 21 by 3, and you get:

x = 7

User Chandra Patni
by
5.3k points
6 votes

Answer:

x=-21, y=35

Explanation:

3x+2y=7 ⇒ 3x+2y=7

y=3-x+11 ⇒ y= -x+14 now we know what y is.

so substitute y for -x+14 and solve the equation:

3x+2(-x+14)=7

3x-2x+28=7

x=-21 so now we know what x is.

Substitute x into y=-x+14 and you get 35, so x=-21, y=35.

Hope this helped!

User Pavel Bredelev
by
7.1k points